PHARMACOLOGICAL ACTIVITY OF AQUEOUS AND ETHANOLIC EXTRACTS OF CALCEOLARIA TRIPARTITA (SACHABERROS) - Tomás, Gloria (2006)
The present research refers to our natural products in order to use them for therepeutics aims. In this proyect the Calceolarie tripartita(Sachaberros) was used to regulate the hepatical function in rats. By fitochemistru analysis has been determined: diterpens, curnarinas, and alkaloids. The cualitative analysis shows minerals macronutrients: iron, potasium, calcium, phosphorus and magnesium.